Faecal incontinence in inflammatory bowel disease: The Nancy experience. Issue 9 (September 2022) - Kurt, Simon; Caron, Bénédicte; Gouynou, Celia; Netter, Patrick; Vaizey, Carolynne J.; Wexner, Steven D.; Danese, Silvio; Baumann, Cédric; Peyrin-Biroulet, Laurent
Abstract: Background: Faecal incontinence (FI) is a disabling condition in patients with inflammatory bowel disease (IBD). The diagnosis of FI is not easy as patients are reluctant to report this embarrassing symptom. The objectives of this study were to characterize the prevalence of FI in IBD patients using available scoring systems, and to identify associated risk factors. Methods: A FI clinic was implemented in routine practice between January 2020 and April 2021. FI was defined as a Wexner score ≥5. Factors associated with FI were analyzed. Results: A total of 319 consecutive patients with IBD were included. The prevalence of FI was 16.4% (53/319). Age >45 years at inclusion (Odd ratio (OR)=3.33, Confidence interval (CI) 95% 1.40–7.94), diarrhea (three stools at least per day) (OR=2.94, CI 95% 1.16–7.45), stool consistency according to the Bristol stool chart (OR=2.23, CI 95% 1.00–4.99), and abdominal pain (OR=2.24, CI 95% 1.10–4.53) were independently associated with FI in a multivariate model analysis. Conclusions: Approximately one fifth of IBD patients reported FI in this real-world cohort, using an available scoring system. Increased age, diarrhea, stool consistency according to the Bristol stool chart, and abdominal pain were associated with FI. A systematic screening of FI would allow a better management of this disabling condition.